Amphibian oocyte maturation and protein synthesis: Related inhibition by cyclic AMP, theophylline, and papaverine - Bravo, Rodrigo (Proc Natl Acad Sci U S A, 1978)
Two inhibitors of cyclic AMP phosphodiesterase (3′:5′-cyclic-AMP 5′-nucleotidohydrolase, EC 3.1.4.17), theophylline and papaverine, inhibit the maturation of Xenopus laevis oocytes induced by four different stimuli: human chorionic gonadotropin, progesterone, testosterone, and lanthanum ions. Addition of 1 mM cyclic AMP to the medium delays maturation by approximately 2 hr. Papaverine, theophylline, and cyclic AMP inhibit amino acid incorporation into oocyte proteins by 50% or more but do not inhibit amino acid uptake. The capacity of theophylline to block maturation and protein synthesis is reversed in a parallel fashion by addition of 1-5 mM calcium ion to the medium. Addition of papaverine, theophylline, and cycloheximide to oocytes at different times after hormonal treatment shows that the step sensitive to blockage by the three drugs is coincident and precedes germinal vesicle breakdown by about 1.5 hr. Theophylline and papaverine do not increase endogenous cyclic AMP levels in oocytes but do block the decrease of cyclic AMP levels observed 3 hr after progesterone treatment. Both drugs inhibit oocyte cyclic AMP phosphodiesterase measured in vivo and severely inhibit the stimulus of calcium uptake caused by progesterone and human chorionic gonadotropin. These results suggest that cyclic AMP, theophylline, and papaverine may block oocyte maturation by inhibiting protein synthesis, possibly via a cyclic AMP-dependent protein kinase as shown in reticulocytes [Datta, A., De Haro, C., Sierra, J. & Ochoa, S. (1977) Proc. Natl. Acad. Sci., USA 74, 1463-1467].